A differential weak measurement system based on Sagnac interferometer for self-referencing biomolecule detection. (13th November 2017) - Li, Dongmei; Guan, Tian; He, Yonghong; He, Qinghua; Zhang, Yilong; Wang, Xiangnan; Shen, Zhiyuan; Yang, Yuxuan; Qiao, Zhen; Ji, Yanhong
Abstract: A differential weak measurement system was presented, exhibiting the self-referencing function for biomolecule real time detection as a label-free optical biosensor. We built a Sagnac interferometer, which limited horizontal ( H ) and vertical ( V ) polarization to propagating along the common path but in opposite directions to realize weak measurements with two measuring channels installed in two corners of this Sagnac interferometer. By introducing two half wave plates into the system alternately with the two channels to convert between H and V polarization, we obtained a differential measurement for phase delay, which could quantitatively characterize the refractive index change corresponding to the concentration of samples in the channels. With this system, a real time monitor of molecule concentration in the dialysis process was accomplished, demonstrating the function of self-referencing, which is important for optical label-free molecule detection in a complex biological sample solution.